Spatialising the Imperial Mode of Living - rethinking a concept - Brand, Ulrich; Wissen, Markus (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
In the introduction to this special section, we present the core idea of the concept “imperial mode of living” (IML) which attempts to explain why and how the reproduction of capitalist societal relations continues to be hegemonic despite the widespread recognition of its destructive tendencies. It is argued that the IML itself can be understood as a spatial category: the imperial mode of living creates asymmetric interdependencies between various places and territories in the global North and the global South, it structures the relationship between different parts of the globe in a way that the mechanisms of reproduction in one part affect societies in others. Along four dimensions – valorisation, accumula- tion and reproduction; hegemony and subjectivation; hierarchization; externalization – we present a conceptual and research heuristic on how the working of the imperial mode of living and its socio-spatial implications can be under- stood. Moreover, it is argued that, given deepening crisis tendencies, the paradigm of a “Green Economy” or “Green Deal“ might serve as dominant imaginary that is able to orientate and unite liberal progressive forces to provide for a sufficient degree of economic coherence and to create new terrains of compromising and ways to deal with conflicts that are favourable to the operation of a green-capitalist regime of accumulation. Such an eco-capitalist modernisation of the imperial mode of living in the global North has also severe socio-spatial implications. At the end of the article, we draw a few conclusions, present some criticisms that were made and give a brief outlook of the prospects of a “green capitalism”.